Spotify as a technology for integrating health, exercise and wellness practices into financialised capitalism - Chris Till (Big Data & Society, 2023)
Spotify dominates the audio streaming industry and offers an almost limitless library of music and other ‘sounds’. They have recently made various interventions into health, exercise and wellness with the development of curated and personalised playlists focused on activities such as running, weightlifting and meditation and guided workouts interspersed with algorithmically generated playlists. This article suggests that the company are developing new means of datafying health, exercise and wellness practices such as monitoring activities, heart rate, mood and broadly the rhythms and tempos of their lives. While this is presented as beneficial to users to provide a more personalised experience, analysis of patent applications, financial statements and promotional materials targeting advertisers and investors suggest other objectives. Audio consumption is combined with the newly datafied activities to ‘bundle’ users into ‘audience commodities’ to be sold to advertisers. Furthermore, such innovations, and the potential to attract advertisers, form the materials through which Spotify construct stories to potential investors about the future profitability, or at least growth in market value, of the company essential for firms integrated into ‘financialised capitalism’. This represents a further opening up of aspects of everyday lives to commercial exploitation through datafication and contributes to an attempt to reposition health-related practices as assets which can be packaged for investment portfolios. The publications analysed in this article demonstrate some of the ways in which Spotify seek to both monitor and shape practices of users to make them more amenable to financialisation.